PENERAPAN MODEL PEMBELAJARAN ONLINE BERBASIS PROYEK UNTUK MENINGKATKAN PRESTASI BELAJAR (Studi Pada Mata Pelajaran Bahasa Inggris Kelas XI Program IPS SMA Negeri 1 Pagaralam) - Maryanto Maryanto; Wasidi Wasidi (DIADIK, 2021)
This study aims to increase learning achievement in English lessons at SMA Negeri 1 Pagaralam by applying a project-based model. The type of research used is classroom action research and quasi eskperiment. This classroom action research was carried out in 3 cycles, each cycle consisting of four stages, namely: Planning, Action, Observation, Reflection, The subjects of this study were Eleventh Grade of Social Program. Data collection using observation sheets and tests. The conclusion of this study is that the project-based model is very effective in increasing learning achievement of students in online learning English for class XI of the Social Studies Program at SMA Negeri 1 Pagaralam